Acetylcholine-induced cation translocation across cell membranes and inactivation of the acetylcholine receptor: chemical kinetic measurements in the millisecond time region. - Cash, D J (1981)
Acetylcholine-induced flux of inorganic ions across membranes and inactivation of the acetylcholine receptor were measured at pH 7.0, 1 degrees C, over a 5000-fold concentration range of acetylcholine. Receptor-containing electroplax membrane vesicles prepared from Electrophorus electricus and a quench-flow technique were used, allowing flux to be measured in the 2-msec to 1-min time region. Five different measurements were made: (i) rate of ion translocation with the active state of the receptor, (ii) rate of the slower ion translocation after equilibration of active and inactive receptor states, (iii) rate of inactivation, (iv) equilibrium between active and inactive forms of the receptor, and (v) reactivation of inactivated receptor. The kinetics of the steps in the receptor-controlled ion flux follow single-exponential rate laws, and simple analytical expressions for their ligand concentration dependence can be used. Thus, the rate and equilibrium constants in a scheme that relates the ligand binding steps to ion translocation could be evaluated. It was found that the dependence of the receptor-controlled ion translocation over the concentration range investigated obeys the integrated rate equation based on the proposed mechanism. The flux rate before inactivation was approximately 10(7) ions sec-1 per receptor, which is comparable with that measured electrophysiologically in muscle cells. The half-time of inactivation is approximately 100 msec when the receptor is saturated with acetylcholine. The specific reaction rate of the ion translocation (J) is 3 X 10(7) M-1 sec-1. The results support a minimum reaction mechanism previously proposed on the basis of experiments in which carbamylcholine was used.